Development and Application of 3D Excavation Design Software Based on Microstation Platform in Water Resources and Hydropower Projects - LYU Bin; FU Zhihao (Renmin Zhujiang)
In order to realize the rapid modeling,quantity calculation,drawing and annotation in the 3D excavation design of water resources and hydropower projects,based on the MicroStation platform,and the .Net-based Addins secondary development method,this paper proposes a design solution,with the development language of C# as the priority,and C++/CLI package as a supplement,including 7 modules of general type,sloping type,auxiliary type,profile type,statistics type,annotation type and earth-rock dam,to meet the functional requirements of the entire excavation design process.Its application on multiple projects shows that the quality of design software and the design efficiency are obviously superior to similar software as follows:①For the design software,the real-time three-dimensional display is,more accurate to express the design intent,the plan and section drawings,and related excavation and support quantities are all extracted from the 3D model.The accuracy of both drawing expression and quantity is better than two-dimensional design;②Compared with traditional methods,the efficiency of excavation design,quantity extraction,and base drawing is improved by more than 70%,and that of drawing is increased by more than 50%.The software development framework,function realization ideas and key technology research are of significant reference for similar projects.